Kajian Perencanaan Tata Ruang untuk Memfasilitasi Kegiatan Non-Pertanian di Kecamatan Sukorejo, Kabupaten Kendal - Ratika Tulus Wahyuhana; Agung Sugiri (Jurnal Wilayah dan Lingkungan, 2014)
Rural non-farm sector is potential to alleviate poverty and improve rural people’s welfare; however, its development is less encouraged by the government policy, especially the regional spatial plans in Indonesia (Sugiri, et al. 2011). The situation also occurs in Sukorejo District (Kecamatan) of Kendal Regency (Kabupaten) as a potential region for developing rural non-farm sector. This study is aimed at answering the research question of: "How can spatial planning facilitate better the development of rural non-farm sector in Sukorejo District?" The approach used is qualitative with qualitative descriptive analysis method. The findings show that the rural non-farm activities in Sukorejo District are able to create siginificant jobs for the local community. However, with regard to the spatial structure, the people engaged in rural non-farm activities perceive that intra- and inter-regional connectivity has not been supporting the acitivities. As for the spatial function, they are of the opinion that the spatial plan has no benefits to offer. So, the constructs of the community show that the spatial plan does not facilitate appropriately the development of rural non-farm activities. In some aspects, especially in the spatial structure, implementation of the spatial plan can even be obstructing. It has also been found out that the planning process was not participatory at all as far as the rural non-farm people are concerned. Therefore, reformulation of the spatial planning process is needed so that the plan can accommodate the community needs in the aspects of input, production, and distribution in the rural non-farm sector. Finally, necessary measures towards the reformulation are recommended in this study.